2010
DOI: 10.1158/1541-7786.mcr-10-0212
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β1–Mediated Activation of NF-κB Contributes to Enhanced ADAM-12 Expression in Mammary Carcinoma Cells

Abstract: A disintegrin and metalloproteinase-12 (ADAM-12), a member of multifunctional family of proteins, is upregulated in many cancers, including breast, lung, liver, prostate, gastric, and bladder. The multidomain structure, composed of a prodomain, a metalloproteinase, disintegrin-like, epidermal growth factor-like, cysteinerich and transmembrane domains, and a cytoplasmic tail, allows ADAM-12 to promote matrix degradation, cell-cell adhesion, and intracellular signaling capacities and thereby to play a critical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
1
17
1
Order By: Relevance
“…On the basis of these data, it has been suggested that in the context of ovarian cancer, mutations and/or alterations of the key nodes along canonical TGF-b pathway shift TGF-b to noncanonical pathways such as activation of NF-kB which describes the pro-oncogenic role of TGF-b in advanced ovarian cancer (38,39). In fact, activation of TGF-b/NFkB pathway has been defined as the underlying mechanism in the phenomenon of conversion of TGF-b from a tumor suppressor to a tumor promoter during tumorigenesis (28,40,41). In our study, it was found that minocycline downregulates the endogenous levels of TGF-b1.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of these data, it has been suggested that in the context of ovarian cancer, mutations and/or alterations of the key nodes along canonical TGF-b pathway shift TGF-b to noncanonical pathways such as activation of NF-kB which describes the pro-oncogenic role of TGF-b in advanced ovarian cancer (38,39). In fact, activation of TGF-b/NFkB pathway has been defined as the underlying mechanism in the phenomenon of conversion of TGF-b from a tumor suppressor to a tumor promoter during tumorigenesis (28,40,41). In our study, it was found that minocycline downregulates the endogenous levels of TGF-b1.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have recently demonstrated that ADAM12 expression is induced by transforming growth factor ␤ (TGF␤) via Smad-dependent and Smad-independent signaling pathways (35)(36)(37)(38)(39). Consistently, ADAM12 induction by TGF␤ is significantly attenuated in Smad2 Ϫ/Ϫ or Smad3 Ϫ/Ϫ MEFs (37).…”
Section: Up-regulation Of Adam12 Expression By Notch Requires New Tramentioning
confidence: 84%
“…Several studies demonstrated that ADAM12 expression is induced by TGF␤, via both Smad-dependent and Smad-independent pathways (35)(36)(37)(38)(39). Interestingly, ADAM12 induction by TGF␤, similar to the induction by Notch, is completely abolished by MG132 (37,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ADAM12 plays a direct profibrotic role, regulating TGF-β signaling 23,42,43 . After TGF-β binds with specific receptors, the signal is transduced to the nucleus by members of the Sma-and Mad-related (Smad) family.…”
Section: Discussionmentioning
confidence: 99%